The Fulfillment of the Freedom of Contract in Indonesia’s Electronic Contract Regulation: An International Law Perspective - Oliviani Yanto; Indirani Wauran (JUSTISI, 2026)
This study aims to analyze the alignment of Indonesia’s regulations on electronic contracts with the UNCITRAL Model Law on Electronic Commerce in order to promote reforms to contract law that are more adaptable to digital developments. The digital transformation has made electronic contracts the primary means of conducting cross-border civil transactions. However, Indonesia’s regulations under the ITE Law are considered to be limited to business transactions and do not yet accommodate other civil relationships. The method used is normative legal research employing legislative, conceptual, and comparative approaches. This study analyzes the UNCITRAL Model Law on Electronic Commerce as an international legal instrument serving as a guideline for harmonization. In addition, this study also examines the ITE Law and its implementing regulations as sectoral regulations, as well as the Indonesian Civil Code as the general legal framework that should ideally serve as the overarching regulatory framework for electronic contracts. The novelty of this study lies in its analysis of the relationship between the principle of freedom of contract in the Indonesian Civil Code and UNCITRAL’s international standards, a topic rarely discussed in the national literature. The results of the study indicate that the UNCITRAL Model Law provides a flexible and universal framework consistent with the principle of freedom of contract; however, its application in Indonesia remains limited by the ITE Law’s focus solely on electronic transactions. The conclusion of this study is that harmonization of Indonesian contract law with international principles is necessary so that the regulation of electronic contracts can apply across sectors, not limited to business, and meet the dynamics of legal globalization.